Mexican American Parental Knowledge and Perceptions of Childhood Obesity: An Integrative Review. (June 2020) - Confiac, Nathalie; Turk, Melanie T.; Zoucha, Rick; McFarland, Marilyn
Introduction: For the past two decades, childhood obesity has remained a national public health concern, particularly among Hispanic populations. Multiple cross-sectoral obesity prevention strategies have been implemented yet remain unsuccessful in generating sustainable lifestyle changes. Method: The purpose of this integrative review, using the Whittemore and Knafl method, was to examine the literature from 2009 to 2018 regarding Mexican American parental knowledge and perceptions of childhood obesity. The CINAHL, PubMed, PsycINFO, and ERIC databases were used to search the literature, and 13 peer-reviewed articles met the inclusion criteria. Results: Three main themes emerged from the literature synthesis: (1) parental misperception of child body weight and size, (2) influence of cultural health and growth beliefs on parental perception of child weight, and (3) parental perspectives of causes and consequences of childhood obesity and how to address it. However, cultural variations in parental perceptions were found; therefore, attempts to generalize Mexican Americans' cultural practices should be avoided. Conclusion: Studies using qualitative approaches are needed to gain deeper insights about Mexican American culture regarding children's health as it relates to body weight, the roles of different family members in the Mexican American childrearing tradition, and the impact of their associated health beliefs.